Relocating women's equality - Gupta, Sadhna; Kumar, Pankaj (Rawat Publications, 2015)
Indian society is still largely male-dominated. Although women constitute half the population, equal opportunity and equal treatment are alien concepts to a large number of women in India. In this scenario, women often have to endure a climate of condescension bordering on contempt and hostility. The Constitution of India did well by declaring in its Preamble its desire to secure justice - social, economic, and political - and to secure equality of status and opportunity. Several steps have been taken to ensure the translation of these objectives into reality, by incorporating provisions that ensure equality of status and of opportunity in the fields of education, public employment, and participation in political life. A number of legislations have been enacted for the protection and emancipation of women. Yet, in spite of the many laws to defend women, crime against women is on the increase. This volume not only reflects upon the real position of women in India, but it also recommends the steps which can help in reducing crime against women and give them equal status in the society. [Subject: India Studies, Women's Studies, Sociology, Human Rights]